Non-Traded Goods and the Transfer Problem - McDougall, I. A. (Review of Economic Studies, 1965)
Journal Article Non-Traded Goods and the Transfer Problem Get access I. A. McDougall I. A. McDougall Australian National University Nuffield College, Oxford Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 32, Issue 1, January 1965, Pages 67–81, https://doi.org/10.2307/2296333 Published: 01 January 1965